2016
DOI: 10.3892/or.2016.4921
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 3 protein modulates human esophageal cancer cell growth by targeting the NF-κB signaling pathway

Abstract: It has recently been found that the expression of the transglutaminase 3 (TGM3) is significantly reduced in esophageal cancer (EC). However, the potential of TGM3 as a useful biomarker or as a molecular target for EC diagnosis and treatment is unclear. The aim of the present study was to explore the role of the TGM3 in EC. The expression level of TGM3 were measured by real-time polymerase chain reaction and western blot analysis in EC cell lines, including SKGT-4, KYSE-510, OE33, OE21 and the normal esophageal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Furthermore, low TGM3 expression is associated with poor overall survival [32]. There is also evidence for TGM3 to induce cell proliferation and migration in esophageal cancer by downregulating the NF-κB signaling pathway [33]. Genome-wide association study (GWAS) of 38.5 million SNPs and small indels identified TGM3 variant as a contributor to risk of basal cell carcinoma [34].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, low TGM3 expression is associated with poor overall survival [32]. There is also evidence for TGM3 to induce cell proliferation and migration in esophageal cancer by downregulating the NF-κB signaling pathway [33]. Genome-wide association study (GWAS) of 38.5 million SNPs and small indels identified TGM3 variant as a contributor to risk of basal cell carcinoma [34].…”
Section: Resultsmentioning
confidence: 99%
“…As a molecular mecha-nism of TG3 repression, hypermethylation of CpG islands within the TGM3 promoter has been proposed [18]. Furthermore, TGM3 was shown as a putative tumour-suppressor gene in oesophageal cancer, in which its expression was downregulated and associated with tumour proliferation and migration [19,20]. Skin cancer is the most common type of cancer.…”
mentioning
confidence: 99%
“…Li et al [ 31 ] demonstrated that TGM-3 can be a candidate tumour suppressor that is able to induce EC cell proliferation and migration by down regulating the NF-κB signalling pathway, indicating that TGM-3 may serve as a useful biomarker and therapeutic target for esophageal cancer treatment.…”
Section: Discussionmentioning
confidence: 99%